Personalized medicine and Type 2 diabetes: lesson from epigenetics. (April 2014) - Raciti, Gregory Alexander; Nigro, Cecilia; Longo, Michele; Parrillo, Luca; Miele, Claudia; Formisano, Pietro; Béguinot, Francesco
Similarly to genetic polymorphisms, epigenetic modifications may alter transcriptional activity and contribute to different traits of the Type 2 diabetes phenotype. The establishment of these epigenetic marks may precede diabetes onset and predict the disease. Current evidence now indicates that epigenetic differences represent markers of diabetes risk. Studies on epigenome plasticity revealed that cytokines and other metabolites, by affecting DNA methylation, may acutely reprogram gene expression and contribute to the Type 2 diabetes phenotype even in the adult life. The available evidence further indicates that epigenetic marks across the genome are subject to dynamic variations in response to environmental cues. Finally, different genes responsible for the interindividual variability in antidiabetic drug response are subjected to epigenetic regulation. Determining how specific epigenetic profiles determine diabetes is a challenging task. In the near future, the identification of epigenetic marks predictive of diabetes risk or response to treatment may offer unanticipated opportunities to personalize Type 2 diabetes management.